Functionally rigid and degenerate molecular shuttles - Stoddart, J. Fraser (2011)
The preparation and dynamic behavior of two functionally rigid and degenerate [2]rotaxanes (1⋅4 PF6 and 2⋅4 PF6) in which a π-electron deficient tetracationic cyclophane, cyclobis(paraquat-p-phenylene) (CBPQT4+) ring, shuttles back and forth between two π-electron-rich naphthalene (NP) stations by making the passage along an ethynyl-phenylene-(PH)-ethynyl or butadiyne rod, are described. The [2]rotaxanes were synthesized by using the clipping approach to template-directed synthesis, and were characterized by NMR spectroscopic and mass spectrometric analyses. 1H NMR spectra of both [2]rotaxanes show evidence for the formation of mechanically interlocked structures, resulting in the upfield shifts of the resonances for key protons on the dumbbell-shaped components. In particular, the signals for the peri protons on the NP units in the dumbbell-shaped components experienced significant upfield shifts at low temperatures, just as has been observed in the flexible [2]rotaxanes. Interestingly, the resonances for the same protons did not exhibit a significant upfield shift at 298 K, but rather only a modest shift. This phenomenon arises from the much reduced binding of the ethynyl-NP unit compared to the 1,5-dioxy-NP unit. This effect, in turn, increases the shuttling rate when compared to the 1,5-dioxy-NP-based rotaxane systems investigated previously. The kinetic and thermodynamic data of the shuttling behavior of the CBPQT4+ ring between the NP units were obtained by variable-temperature NMR spectroscopy and using the coalescence method to calculate the free energies of activation (ΔGc≠) of 9.6 and 10.3 kcal mol−1 for 1⋅4 PF6 and 2⋅4 PF6, respectively, probed by using the rotaxane's α-bipyridinium protons.